PENERAPAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI DI PAUD NURUL ISLAM KOTA PAGAR ALAM - Siti Hanipah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
This research raises  the  issue  of Implementation of Islamic  religious  education in early  childhood in Nurul Islam Early Childhood  School of Pagar Alam. This study used  qualitative research methods to understand the phenomenon of what is experienced by research subjects. Techniques of data collection that used were interviews, observation and documentation. From the results of this study, it indicated that the implementationof Islamic religious education in early childhood in Nurul Islam Early Childhood  School of Pagar Alam by guiding and implementing the teachings of Islam prescribed, like teaching good morals to children, fardlu prayers properly, training children to learn the Qur’an by Iqro.Inhibiting factors in implementing early childhood religious education is an internalfactor, in the form of awareness and understanding of each individual to perform religious teachings, such as the five daily prayers, learn to read the Qur’an and doing good to others.  While external factors, the form of guidance and attention from parents, relationships in the community around them,  and the education obtained from the school.  The efforts to overcome the obstacles in implementing early childhood religious education is to provide exemplary and attention and affection to the child, so they can follow what was ordered by parents and teachers